Thoughts on “Onelessness” - Okazaki, Miles (Revue musicale OICRM, 2025)
These field notes describe a situation where the members of an ensemble have conflicting views on the rhythmic orientation of the material, including the time signature and the beginning of the time cycle. One argument presented is that these conflicts can be productive for producing rhythmic tension and dynamism. The example discussed is a rhythmic figure that the composer has made to intentionally create two opposing and equally valid interpretations of the rhythmic flow within the band. The video examples show this groove evolving over time, and demonstrate a form of ensemble playing where there is no absolute tempo or time signature, but the group is still synchronized, executing detailed contrapuntal information, and functioning creatively.